DOI: 10.14264/uql.2017.499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring registered nurses’ attitudes to postgraduate education for specialty practice in Australia

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 286 publications
(530 reference statements)
0
3
0
2
Order By: Relevance
“…The financial support also enabled participants to balance their work and study commitments by reducing their paid work hours. The conflicting time demands of work and study has been found to prevent nurses and allied health professionals from engaging in postgraduate study (Foreman et al , 2017; Ng et al , 2016; Ng, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The financial support also enabled participants to balance their work and study commitments by reducing their paid work hours. The conflicting time demands of work and study has been found to prevent nurses and allied health professionals from engaging in postgraduate study (Foreman et al , 2017; Ng et al , 2016; Ng, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bu bakımdan lisansüstü eğitim, belli bir alanda yetişmeyi ve uzmanlaşmayı amaçladığı için lisans düzeyinde elde edilen yeterliklerden ayrılmaktadır (Gradschools com., 2019;İlter, 2019). Araştırmalar, lisansüstü eğitimin bireylerin kişisel ilişkilerini, akademik ve sosyal yaşamlarını önemli ölçüde değiştirdiğini ve uzmanlıklarını artırdığını göstermiştir (Chaboyer ve Retsas, 1996;Ng, 2016).…”
Section: Lisansüstü Eğitim Ve öNemiunclassified
“…With regard to academic career, having a postgraduate education is being deemed important as it improves the diverse academic experience peculiar to the fields of specialisation of the individuals, ensuring progress in the track of academic career (Artess & Hooley, 2017;Cragg & Andrusyszyn, 2004) and improving individuals, intellectual and cultural wealth, and ensuring lifelong learning opportunities (Aitken, Currey, Marshall & Elliott, 2008). In addition, postgraduate education significantly diversifies the academic and social lives of individuals by bringing in high competency regarding knowledge and technical skills in a specific field of specialisation, and by providing professional development opportunities (Battie & Steelman, 2014;Ng, 2016;Van Bragt, Bakx, Teune, Bergen & Croon, 2011). Moreover, it is being emphasised in the literature that postgraduate education increases job satisfaction and improves leadership skills and self-sufficiency (Armstrong & Adam, 2002;Cotterill-Walker, 2012).…”
Section: Relationship Between Academic Career Awareness and Academic Career Interestmentioning
confidence: 99%